Congenital Nasolacrimal Duct Obstruction: Comparison of Two Different Treatment Algorithms - Napier, Maria L.; Armstrong, David J.; McLoone, Sean F.; McLoone, Eibhlin M. (Journal of pediatric ophthalmology and strabismus, 2016)
To clarify the most appropriate treatment regimen for congenital nasolacrimal duct obstruction (CNLDO). A retrospective observational analysis was performed of patients undergoing probing with or without intubation to treat CNLDO in a single institution (Royal Victoria Hospital, Belfast) from 2006 to 2011. Based on exclusion criteria, 246 eyes of 177 patients (aged 0 to 9.8 years with a mean age of 2.1 years) were included in this study: 187 (76%) eyes had successful outcome at first intervention with primary probing, whereas 56 (23%) eyes underwent secondary intervention. There were no significant differences by gender, age, or obstruction complexity between the successful and unsuccessful patients with first intervention. For those patients requiring secondary intervention, 16 of 24 (67%) eyes had successful probing, whereas 22 of 24 (92%) had successful intubation. Patients with intubation as a secondary procedure were significantly more likely to have a successful outcome (P = .037). Statistical analysis was performed using the Fisher's exact test and Barnard's exact test. Primary probing for CNLDO has a high success rate that is not adversely affected by increasing age. This study also indicates that if initial probing is unsuccessful, nasolacrimal intubation rather than repeat probing yields a significantly higher success rate. [J Pediatr Ophthalmol Strabismus. 2016;53(5):285-291.].